Political Rhetoric, Armed Violence and Threats to Democracy: An Analysis of Stochastic Terrorism Within the Media Ecosystem - Tatik Tatik; Rifqi Rifqi; Dinata Firmamansyah; Rosidin Rosidin; Sumarta Sumarta (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
This research is motivated by the rise of political violence fueled by the convergence of inflammatory political rhetoric and firearm accessibility. In the digital era, political communication has shifted from policy persuasion to an instrument of dehumanization that threatens the stability of deliberative democracy. This study aims to analyze how socio-psychological mechanisms and media ecosystems contribute to the phenomenon of contemporary political violence. The research method employed is a qualitative approach with library research. Secondary data were gathered from reputable scientific literature, policy reports, and relevant textbooks. Qualitative content analysis was conducted by integrating cognitive-neoassociation theory, totalism theory, and deliberative democracy theory to map the causality between mass communication patterns and the probability of violence. The results indicate that extreme political rhetoric creates a "siege mentality" that dehumanizes political opponents as existential threats. This phenomenon is validated as stochastic terrorism, where social media algorithms act as incubators for radicalization that trigger lone-wolf violent actions. The availability of firearms further exacerbates the situation by providing physical capability to ideologically radicalized individuals. In conclusion, the threat to democracy today is systemic, originating from the erosion of communication norms at the elite level to the manipulation of information in the digital sphere. Effective mitigation requires the construction of political "cooling structures," media algorithm regulation, and the restoration of discursive ethics to return human dignity to the political arena.